Study on How Physical Transport Infrastructure Impact on Logistics Transport Development: The Case of Ho Chi Minh, Vietnam - Hanh, Vu Thi Kim (Modern Perspectives of Logistics Transport in Economics. Empirical Studies in Ho Chi Minh, Vietnam Vol. 2, 2021)
The objective of this paper is to assess how physical infrastructure impact on logistics transport development; the case of Ho Chi Minh-Vietnam (HCM). Author uses Multivariate regression (MR) to assess by separated MR models, respectively. The major findings are cargo productivity / total labour is are impacted by road length, road quality, length of the railway line, quality of the airway. Passenger productivity / total labour is impacted by road length, road quality, length of the railway line, airlines units which departing internationally, quality of the airway, connection between domestic and international airports. Cargoproductivity / total capital is impacted by road length, road quality, length of the railway line, airlines units which departing internationally, quality of the airway, connection between domestic and international airports. Passenger productivity / total capital is impacted road length, length of the railway line, railway quality, quality of the airway, connection between domestic and international airports.All of eight independent variables PI1, PI2, PI3, PI4, PI5, PI6, PI7, PI8impact onGDP of logistics transport in HCM.